Methylation in MIRLET7A3 gene induces the expression of IGF-II and its mRNA binding proteins IGF2BP-2 and 3 in hepatocellular carcinoma - Waly, Amr A.; Breuhahn, Kai (Frontiers in physiology, 2019)
miR-let-7a is a tumor suppressor miRNA with reduced expression in most cancers. Methylation of MIRLET7A3 gene was reported to be the cause of this suppression in several cancers; however, it was not explicitly investigated in Hepatocellular Carcinoma (HCC). We aimed at investigating miR-let-7a expression and molecular mode in HCC, identifying drug-targetable networks, which might be affected by its abundance. Our results illustrated a significant repression of miR-let-7a, which correlated with hypermethylation gene of origin MIRLRT7A3. This was further supported by the induction of miR-let-7a expression upon treatment of HCC cells with a DNA-methytransferase inhibitor. Using a computational approach, insulin-like growth factor (IGF)-II and IGF-2 mRNA binding proteins (IGF2BP)-2/-3 were identified as potential targets for miR-let-7a that was further confirmed experimentally. Indeed, miR-let-7a mimics diminished IGF-II as well as IGF2BP-2/-3 expression. In conclusion, this study suggests that DNA hypermethylation leads to epigenetic repression of miR-let-7a in HCC cells, which, induces the oncogenic IGF-signaling pathway.